USING STUDENT SATISFACTION QUESTIONNAIRE TO MANAGE THE LECTURER’S PERFORMANCE - Muizzudin (Krisnadwipayana International Journal of Management Studies, 2021)
The concept of student satisfaction is too broad covering facilities, lecturers, and others. This paper focuses only on managing the lecturer’s performance based on student satisfaction towards what normally a lecturer has done in teaching. The research is aimed at evaluating the lecturer performance in teaching English 2 based on the students’ observation during the online course as the effect of COVID Thecollecteddata from the questionnaire provided for the students is analyzed by using Importance-Performance Grid. The results reveal that the weakness and strength areas of the lecturer can be mapped in four classifications: first, what the lecturer should improve because the lecturer’s performance perceived by the students is in the low level and the students’ expectation is in the high level; second, what the lecturer should maintain or keep going because the lecturer’s performance and the students’ expectation at the same time are in the high level; third, what the lecturer should maintain but think about the weighting of it because the lecturer’s performance is in the low level and the students’ expectation is also in the low level; fourth, what the lecturer should reduce the emphasis if possible because the lecturer’s performance is in the high level and the students’ expectation is in the low level. This research is one of the first attempts to explore what the lecturer can do to improve the performance accordingly in measurable and manageable way by the lecturer himself/herself.